RELATIONSHIP OF CLINICAL COURSE AND BIOMARKERS OF ISCHEMIC STROKE RISK IN PERSONS OF YOUNG AGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In recent years, the problem of stroke in the young, in particular, issues study the I biomarker of risk of ischemic stroke, given a lot of attention due to its insufficient knowledge and a steady increase in the number of cases among people of working age. The purpose and research was to determine the values of homocysteine and BDNF as a biomarker s risk of ischemic stroke in young adults. A total of 123 patients with ischemic stroke in the acute period were examined. The control group consisted of 5 4 young people without cerebrovascular pathology. The research results showed, H the levels of homocysteine and BDNF has age characteristics and has a correlation relationship with the severity of neurological deficit. The data obtained will make it possible to develop an algorithm for a differentiated approach to the prevention of cerebrovascular pathology and to reduce the risk of ischemic stroke in young people.